رحلات الشيخ عبد الحميد بن باديس وآثارها 1908-1940 - خامسة, رضا; بدرة, عبد الرحمان (جامعة الوادي university of Eloued, 2022)
الملخص: يكتسي موضوع رحلات الشيخ عبد الحميد بن باديس وآثارها أهمية كبيرة، حيث يعتبر من أهم المواضيع الهامة والحساسة في تلك الحقبة التاريخية، وذلك من خلال الكشف على جانب مهم عن رحلات الشيخ، وآثارها على المجتمع الجزائري، ونهدف من خلال هذه الدراسة الى تسليط الضوء على أهم المحطات التي نزل عندها الشيخ عبدالحميد بن باديس في رحلاته في الفترة (1908-1940) وكذلك الى إبراز أهمية رحلاته في تحقيق أهداف مشروعه الإصلاحي وتجاوزه مختلف العوائق التي اعترضته من طرف السلطات الفرنسية ومعاونيها في رحلاته وبينا مدى تأثير رحلاته على المجتمع الجزائري. The subject of the travels of Sheikh Abdul Hamid bin Badis and their effects is of great importance, as it is considered one of the most important and sensitive topics in that historical era, by revealing an important aspect of the Sheikh’s travels, and their effects on the Algerian society, and through this study, we aim to shed light on the most important stations that Sheikh Abdul Hamid bin Badis visited in the period (1908-1940), as well as to highlight the importance of his trips in achieving the goals of his reform project and overcoming the various obstacles he encountered by the French authorities and their assistants in his trips, and we showed the impact of his trips on the Algerian society.
مذكرة ماستر تاريخ تخصص المغرب العربي المعاصر
Keywords: عبد الحميد بن باديس; Abdelhamid Ben Badis; Abdelhamid Ibn Badis